A Pilot Follow‐Up Study of Older Alcohol‐Dependent COGA Adults. (30th June 2019) - Chan, Grace; Kramer, John R.; Schuckit, Marc A.; Hesselbrock, Victor; Bucholz, Kathleen K.; Edenberg, Howard J.; Acion, Laura; Langbehn, Douglas; McCutcheon, Vivia; Nurnberger, John I.; Hesselbrock, Michie; Porjesz, Bernice; et al.
Abstract : Background: Alcohol consumption and problems are increasing among older adults, who are at elevated risk for alcohol‐related accidents and medical problems. This paper describes a pilot follow‐up of older adults with a history of alcohol dependence that was designed to determine the feasibility of conducting a more extensive investigation. Methods: The sample consisted of previously assessed subjects in the Collaborative Studies on the Genetics of Alcoholism who: (i) were age 50+; (ii) had lifetime DSM‐IV AD; and (iii) had DNA available. Individuals were located through family contacts, Internet searches, and death registries. A brief telephone interview assessed demographics, health, and alcohol involvement. Results: Of the total sample ( N  = 2, 174), 36% were contacted, 24% were deceased, and 40% were not yet located. Most (89%) contacted subjects were interviewed, and 99% of them agreed to future evaluation. Thirty percent of interviewed subjects reported abstinence for 10+ years, 56% reported drinking within the past year, and 14% last drank between >1 and 10 years ago. There were no age‐related past‐year differences in weekly consumption (overall sample mean: 16 drinks), number of drinking weeks (30.8), maximum number of drinks in 24 hours (8.1), or prevalence of weekly risky drinking (19%). Among those who drank within the past 5 years, the 3 most common alcohol‐related problems were spending excessive time drinking or recovering (49%), drinking more/longer than intended (35%), and driving while intoxicated (35%); and about a third (32%) received some form of treatment. Conclusions: Over a 1‐year period, we located 60% of individuals last seen an average of 23 years ago. The majority of contacted individuals were interviewed and willing to be evaluated again. Although the proportion of individuals currently drinking diminished with age, subjects exhibited troublesome levels of alcohol consumption and problems. Our findings suggest the importance and feasibility of a more comprehensive follow‐up. Abstract : This paper describes a pilot follow‐up of older adults with a history of alcohol dependence that was designed to determine the feasibility of conducting a more extensive investigation. Although the proportion of individuals currently drinking diminished with age, subjects exhibited troublesome levels of alcohol consumption and problems. Our findings suggest the importance and feasibility of a more comprehensive follow‐up.